2022
DOI: 10.3389/fcell.2022.884360
|View full text |Cite
|
Sign up to set email alerts
|

The Golgi Apparatus and its Next-Door Neighbors

Abstract: The Golgi apparatus represents a central compartment of membrane traffic. Its apparent architecture, however, differs considerably among species, from unstacked and scattered cisternae in the budding yeast Saccharomyces cerevisiae to beautiful ministacks in plants and further to gigantic ribbon structures typically seen in mammals. Considering the well-conserved functions of the Golgi, its fundamental structure must have been optimized despite seemingly different architectures. In addition to the core layers o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(32 citation statements)
references
References 218 publications
(284 reference statements)
1
31
0
Order By: Relevance
“…Most de novo synthesized secretory and vacuolar proteins begin their journey from the ER, mediated by COPII-coated vesicles ( Barlowe et al, 1994 ; Bethune and Wieland, 2018 ). Subpopulations of ER- and Golgi-resident proteins cycle between the ER and Golgi, and COPI-coated vesicles mediate retrograde transport from the Golgi to the ER ( Matsuura-Tokita et al, 2006 ; Glick and Nakano, 2009 ; Ishii et al, 2016 ; Nakano, 2022 ). The COPI coat is also responsible for the intra-Golgi transport of Golgi-resident enzymes/proteins between Golgi cisternae.…”
Section: Discussionmentioning
confidence: 99%
“…Most de novo synthesized secretory and vacuolar proteins begin their journey from the ER, mediated by COPII-coated vesicles ( Barlowe et al, 1994 ; Bethune and Wieland, 2018 ). Subpopulations of ER- and Golgi-resident proteins cycle between the ER and Golgi, and COPI-coated vesicles mediate retrograde transport from the Golgi to the ER ( Matsuura-Tokita et al, 2006 ; Glick and Nakano, 2009 ; Ishii et al, 2016 ; Nakano, 2022 ). The COPI coat is also responsible for the intra-Golgi transport of Golgi-resident enzymes/proteins between Golgi cisternae.…”
Section: Discussionmentioning
confidence: 99%
“…Then, the endocytic cargo α-factor is transported to the Vps21p-residing compartment dependent on GGA adaptors although whether they directly bind to the cargo is unclear, while Snc1p is transported to the PM. A recent study demonstrated that in plants the TGN has at least two subregions (zones) responsible for secretory and vacuolar trafficking (Nakano, 2022; Shimizu et al, 2021), and endocytic cargo transport via the Tlg2p sub-compartment might mediate this later zone. We recently reported that Vps9p, a GEF for Vps21p, is recruited to the TGN, and then transported to the endosome to activate Vps21p through Ent3p/5p-mediated vesicle transport (Nagano et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…It is made available under a preprint (which was not certified by peer review) is the author/funder, who has granted bioRxiv a license to display the preprint in The copyright holder for this this version posted November 21, 2022. ; https://doi.org/10. 1101/2022…”
Section: Videomentioning
confidence: 99%
“…Finally, MVBs are integrated in the cell membrane, a phenomenon that leads to the secretion of exosomes in the extracellular space via exocytosis. This step requires the involvement of soluble NSF attachment protein receptor (SNARE) proteins such as Ykt6, VAMP7, and syntaxin 1A (Syx1A), which have a key role in the fusion of MVBs with the cell membrane [ 29 , 30 ]. However, MVBs can be possibly led to lysosomes for degradation, or can be fused with autophagosomes [ 31 ].…”
Section: An Overview Of Extracellular Vesicle Biogenetic Mechanismsmentioning
confidence: 99%